Candida albicans: risk factor in COVID-19 patients - San Martín Andrade, Daniela (2022)
To relate the presence of Candida Albicans as an aggravating factor in patients with COVID-19, a bibliographic review was carried out in the Redalyc, Scielo, PubMed, Research gate, Science direct, Google scholar databases. The inclusion criteria used were: articles in English and Spanish as well as articles published from 2020 to date. 65 scientific articles that met the search criteria were analyzed and it was possible to determine that Oral candidiasis negatively affects patients with COVID-19 infection, increasing the risk of admission to the ICU with the use of artificial ventilators.